Influenza Therapeutics and Challenges - Saxena, Shailendra K. (Infectious Diseases, 2018)
This book gives a comprehensive overview of recent advances in influenza, as well as general concepts of molecular biology of influenza infections, epidemiology, immunopathology, prevention, and current clinical recommendations in management of influenza, including preparation of vaccines, assessment of the safety and quality of influenza vaccines and adjuvants highlighting the ongoing issues and recent advances, with future directions in prevention and therapeutic strategies. I hope that this work might increase the interest in this field of research and that the readers will find it useful for their investigations, management, and clinical usage.